A chronic and painless form of idiopathic brachial plexus neuropathy. Issue 6 (June 1983) - Schott, G D
Abstract : Three patients are reported who developed slow and painless weakness and wasting of the muscles of one shoulder girdle, denervation in the affected muscles, and subsequent complete recovery. In two patients, an area of cutaneous sensory loss in the distribution of the circumflex nerve was detected. No underlying cause was found, and it is suggested that these features represent an unusual chronic and painless variant of idiopathic brachial plexus neuropathy.